2020
DOI: 10.1155/2020/7302828
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Restless Legs Syndrome among Medical Students of Karachi: An Experience from a Developing Country

Abstract: Background. Restless legs syndrome (RLS) is a neurological disorder characterized by an uncomfortable sensation in the legs which gets worse in the evening or night, relieved upon movement. The aim of this study was to specify the prevalence of RLS in the group of young medical students and to assess the effect of RLS on sleep, as sleep disturbance is one of the chief complaints of RLS patients. We also studied its association with smoking as it is considered an aggravating factor. Method. This was a cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…All but two of our studies relied on data from face‐to‐face interviews, telephone interviews, self‐reports, or postal questionnaires, although based on relevant diagnostic criteria and validated tools, the use of patient's self‐assessments in the results can be seen as doubtful. The two studies that used clinical assessments (Erer et al, 2009; Ishaq et al, 2020), which might have included a more thorough examination both showed lower prevalence. Second, the retrospective nature of the study, including data from 2000 until 2022, meant that half of the included studies relied upon data from the IRLSSG four essential diagnostic criteria for RLS.…”
Section: Discussionmentioning
confidence: 99%
“…All but two of our studies relied on data from face‐to‐face interviews, telephone interviews, self‐reports, or postal questionnaires, although based on relevant diagnostic criteria and validated tools, the use of patient's self‐assessments in the results can be seen as doubtful. The two studies that used clinical assessments (Erer et al, 2009; Ishaq et al, 2020), which might have included a more thorough examination both showed lower prevalence. Second, the retrospective nature of the study, including data from 2000 until 2022, meant that half of the included studies relied upon data from the IRLSSG four essential diagnostic criteria for RLS.…”
Section: Discussionmentioning
confidence: 99%
“…This considerable difference underscores the variation in the prevalence of sleep-disordered breathing between these two groups of students in different geographic locations. Besides, disturbed sleep-disordered breathing depends on risk factors such as snoring, body mass index (BMI), age, and gender [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep-related breathing is strongly connected with lower academic performance among schoolchildren [ 46 ]. Several factors, including age, gender, socioeconomic status, race, and BMI, can impact the association between sleep-disordered breathing [ 35 , 47 , 48 ] and academic performance, which needs additional investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Restless leg syndrome (RLS) is a neurological disease characterized by throbbing, pulling, creeping, or other unpleasant sensations in the legs and an uncontrollable and sometimes overwhelming urge to move them [1] . It was first described by Sir Thomas Willis, an English physician in 1672 [2] .…”
Section: Introductionmentioning
confidence: 99%